Aristophanes Vespae 530: The Mysterious Voice and Person - Szymański, Mikołaj (Polskie Towarzystwo Filologiczne, 2022)
A conjecture is proposed in order to cure grammatical problems with the form φανεῖ in Ar. V. 530.